The Ijmali Tafsir Method: Its History, Importance, Steps, Benefits, and Drawbacks in the Interpretation of the Qur'an - Husna, Nida Ul (UIN Sunan Gunung Djati Bandung, 2024)
This research comprehensively discusses the method of ijmali interpretation in interpreting the Qur'an. With a focus on history, urgency, steps, as well as its strengths and weaknesses, this research explores the method of interpretation that emerged at the beginning of the revelation of the Qur'an, when the Muslim community at that time had a profound understanding of the Arabic language and directly witnessed the events of the revelation. The ijmali interpretation method is analyzed as a global, practical, and easily understandable approach, revealing synonyms, asbabun nuzul, and the core message of the verses briefly. Although this method is simple and needs more opinions of interpreters, its weakness lies in the limitation of providing in-depth explanations. This research utilizes a literature review study to detail the key aspects of the ijmali interpretation method, providing a deeper understanding of this approach in uncovering the meanings of the Qur'an.